Cellphones, radars, and health. - Kasevich, R.S.
Exposure standards for electromagnetic radiation do not adequately address current realities. These standards are based on conclusions drawn from many experiments in the decades after World War II. Few of those studies, however, were designed to study low-level, localized biological effects not linked to heat. But electromagnetic theory and decades of experiments clearly indicate that the electromagnetic fields of radio and microwaves can also affect cells mechanically, without producing significant amounts of heat.
Keywords: World War II; Biological cells; Cellphones; Electromagnetic fields; Electromagnetic radiation; Electromagnetic theory; Exposure standards; Health effects; Localized biological effects; Low-level biological effects; Microwaves; Radar; Radio waves